Genome editing in cultured fishes - Eric Hallerman (CABI Agriculture and Bioscience)
Abstract With external fertilization, high fecundity, and established methods for propagation and larval rearing for cultured species, fish provide systems well suited to genome-editing procedures. While early experiments utilized zinc-finger nucleases and transcription activator-like effector nucleases (TALENs), most recent ones have used the CRISPR/Cas9 editor, and achieved rates of targeted genomic insertion well above those of classical transgenic methods, with lower frequencies of off-site integration. Genome-editing experiments with cultured fishes have focused on improving growth rate and disease resistance, achievement of reproductive confinement, and other valued traits. As reviewed here, advances in knowledge of key molecular pathways and, in some cases, favorable alterations of phenotype have been achieved. For example, loss-of-function of myostatin, a negative regulator of muscle growth, led to increased muscle mass, greater weight, and greater fillet yield in genome-edited lines of red sea bream, tiger puffer, and Nile tilapia than in their unedited counterparts. The red sea bream line become the first genome-edited animal to reach commercial production. As for all animals, wide adoption of genome-edited fishes will depend upon addressing issues of regulation, consumer acceptance, and breeding infrastructure.